(3GdeMGSHI GdMchejI Hjf GdfXQjI hGdJWHjb s - (3YHO GdMdje eMehO(B, (3cQGLIs ((3GQHO(B:s (3OGQ GdCed(B,s, 1997)
(3eONd aj GdeMGSHI GdMchejI,GdehGRfI GdYGeI ddOhdI,GdbhGYO GdCSGSjI ddehGRfI hJYQjagG,JHhjH GdehGRfI GdYGeI,JWhQ GdehGRfI GdYGeI ddOhdI,GdehGRfI GdYGeI aj GdCQOf,EYOGO GdehGRfI GdYGeI,GdfXGe GdeMGSHj GdMchej,GdQbGHI GdOGNdjI,GdQbGHI Ydi GdeJMUdGJ GdfbOjI hZjQ GdfbOjI,GdQbGHI GdOGNdjI ddOjhf GdMchejI hGdOaGJQ PGJ GdbjeI,GdQbGHI Ydi eNGRf GdOhdI,GdMSGHGJ GdhSjWI,JObjb MSGHGJ GdHfc,GdJShjGJ GdeMGSHjI,JUMjM GdCNWGA(B-(3GdQbGHI Ydi JfajP GdehGRfI GdYGeI ddOhdI,QbGHI hRGQI GdeGdjI,QbGHI OjhGf GdeMGSHI,QbGHI GdSdWI GdJTQjYjI,GdMSGH GdNJGej ddOhdIs
(3GdeQGLY U(B.211s
Keywords: (3GdGQOf (B- (3GdehGRfI GdYGeI s; (3GdeMGSHI GdMchejIs